Hubungan Kualitas Layanan Dan Citra Rumah Sakit Terhadap Kepuasan Pasien BPJS Rawat Jalan RSUD Budhi Asih Tahun 2022: The Relationship Between Service Quality and Hospital Image on Patient Satisfaction Outpatient BPJS Budhi Asih Hospital in 2022 - Rodiah, Siti (Dohara POAJ, 2022)
Introduction: According to the survey on the satisfaction of respondents and health organizations that have been carried out by the BPJS, Myriad Research Committed in 2018 with a total of 17,280 public respondents, 81% said they are satisfied with BPJS outpatient health services. It's still below the government's target for public satisfaction, which is 95%. This suggests the service given by the BPJS is not optimal.1 In improving the quality of health care, Budhi Asih Hospital has applied the quality of services to achieve the goals of service performance and to achieve service satisfaction. They include client satisfaction in outpatient care and improved hospital image. Satisfied patients benefit hospitals, including reusing services given in the future when they need them again and can encourage others to use the service. On the other hand, dissatisfaction with patients will also make it difficult for hospitals to compete. If the impact is not overcome immediately, the hospital's stability will be affected. Disappointed customers don't just go, but tell others about the bad services they receive. Thus, good health care will bring the patient back into use and even encourage others to use it again. The purpose of this study was to determine the relationship of service quality based on the variables of physical evidence, reliability, responsiveness, assurance, empathy, and hospital image to the satisfaction of outpatient BPJS patients at Budhi Asih Hospital in 2022. Methods: This research method uses a descriptive-analytic research method with a cross-sectional approach. The population in this study is 584 respondents. It used the slovin method to obtain a sample of 86 respondents. Data analysis uses univariate and bivariate analysis with a Chi-Square research test. Results: Based on the results of the study, it is known that there is a relationship between service quality from physical evidence (p = 0,002); reliability (p = 0,000); responsiveness (p = 0,000); assurance (p = 0,000); empathy (p = 0,000); and hospital image (p = 0,000) on patient satisfaction. There are significant relationships between service quality and hospital image toward patient satisfaction at Budhi Asih Hospital in 2022. Discussion: It is hoped that the results of this study can be input so that the management of Budhi Asih Hospital can evaluate the service quality and image of the hospital so that it can increase patient satisfaction.